Influence of individualized training on psychomotor performance of young soccer players - Andrzejewski, M.; Chmura, J.; Wiacek, M.; Zubrzycki, I. Z. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to analyze the influence of individualized training (IT) on psychomotor performance of young soccer players. Psychomotor performance was measured by means of differential response time and number of correct responses to audio and visual stimuli. Kinematic analysis allowing assessment of both the distances and the average speeds of young players during consecutive matches was also performed. For the data analysis, one-way analysis of variance, Friedman test, and t-test for dependent samples were used. The obtained results clearly indicate that IT during the preparation period increases specific psychomotor performance among young soccer players.